Determinants of Risk and Uncertainty in Oil Palm Nursery (2014)
Nigeria is the fourth largest producer of palm oil in the world after Indonesia, Malaysia and Thailand in the order of annual production volume. The industry provides direct and indirect employment to about four million people in twenty-four oil palm growing states in Nigeria and beyond. However, oil palm production commences with planting and nurturing of oil palm seedlings in nursery, which is associated with risk and uncertainty. This study investigates the major determinants of risk and uncertainty in oil palm nursery using To bit regression model. Findings show that the major determinants of risk and uncertainty in oil palm nursery were incidence of pests, cost of sprouted seeds, lack of financial capital and seed adulteration. Therefore, it is recommended that management of risk and uncertainty in oil palm nursery should involve purchasing sprouted seed from the right source, pest and disease control and ample provision of financial capital